GREEN INVESTMENT DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN: PROFITABILITAS SEBAGAI PEMEDIASI - ADELLIA TANASYA; SUSI HANDAYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The purpose of this study determines the effect of corporate governance and green investment on firm value with profitability as a mediating variable. Corporate governance variables are proxied by independent commissioners, audit committees, managerial ownership, and managerial ownership. While the green investment variable is proxied by PROPER rating. This study uses 40 samples of companies registered in the 2014-2018 SRI KEHATI Index. The data analysis technique used is path analysis and multiple tests. The results of the study prove that corporate governance and green investment affect profitability, profitability influences peer value, and profitability can mediate the relationship between green investment and firm value.